A Generalized q-Grüss Inequality Involving the Riemann-Liouville Fractional q-Integrals - Aydin Secer; S. D. Purohit; K. A. Selvakumaran; Mustafa Bayram (Journal of Applied Mathematics)
The aim of this paper is to establish q-extension of the Grüss type integral inequality related to the integrable functions whose bounds are four integrable functions, involving Riemann-Liouville fractional q-integral operators. The results given earlier by Zhu et al. (2012) and Tariboon et al. (2014) follow the special cases of our findings.